The Effect of Proposed Exercises According to Hierarchal Training Using Weights For Developing Legs' Explosive Power And Spiking Accuracy In Volleyball - Mohameed, Hazim; Star, Khalil; Abdulghani, Muhanned Yaseen (Journal of Physical Education, 2016)
The importance of the research lies in hierarchal training style using weights fordeveloping legs explosive power and spiking in volleyball. The problem of the research wasin the weakness in jumping power during spiking. The research aimed at designing specialexercises using weights according to hierarchal style for developing legs explosive powerand spiking accuracy as well as identifying the effect of these exercises on the developmentof legs explosive power and spiking accuracy. The researchers hypothesized statisticaldifferences between experimental and controlling group in pre and posttests in favor of theexperimental group and posttests. The researchers used the experimental method on (12)volleyball players from Al Bea club. The results showed positive effect of hierarchal on legsexplosive power and spiking skill in volleyball.